2017
DOI: 10.1080/1554480x.2017.1283998
|View full text |Cite
|
Sign up to set email alerts
|

Playlinks: a theatre-for-young audiences artist-in-the-classroom project

Abstract: Playlinks, the project documented in this paper, contributed a theatre-based artist-in-the-classroom study to the Community Arts Zone initiative. Playlinks involved 248 elementary school classrooms in pre-and post-production workshops connected to live theatre that visited their schools. Data sources included researcher field notes, teacher evaluation forms, and interviews with both teachers and theatre personnel. Findings focus on teacher perceptions of three topics: (a) student engagement, (b) learning acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The practice of having an artist as a member of the pedagogic team in the preschools of Reggio Emilia has inspired many arts and ECEC collaborations across the globe (Churchill-Dower 2009). Projects include Playlinks in Ontario, Canada (McLauchlan 2017); artist in residence programmes in the USA (Eckhoff 2009), Little Big Bang, England (Young 2012), and the Helsinki Arts Education Project, Finland (Nevanen et al 2014). However, factors such as inconsistent funding for both sectors (Arts Council 2005), the focus on academic subjects (McLauchlan 2017) and uncertainty of the role of the artist when working in the ECEC setting (Petrie and Chambers 2010) have led to various models of how artists are involved in the ECEC setting and for how long (Remer 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The practice of having an artist as a member of the pedagogic team in the preschools of Reggio Emilia has inspired many arts and ECEC collaborations across the globe (Churchill-Dower 2009). Projects include Playlinks in Ontario, Canada (McLauchlan 2017); artist in residence programmes in the USA (Eckhoff 2009), Little Big Bang, England (Young 2012), and the Helsinki Arts Education Project, Finland (Nevanen et al 2014). However, factors such as inconsistent funding for both sectors (Arts Council 2005), the focus on academic subjects (McLauchlan 2017) and uncertainty of the role of the artist when working in the ECEC setting (Petrie and Chambers 2010) have led to various models of how artists are involved in the ECEC setting and for how long (Remer 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Projects include Playlinks in Ontario, Canada (McLauchlan 2017); artist in residence programmes in the USA (Eckhoff 2009), Little Big Bang, England (Young 2012), and the Helsinki Arts Education Project, Finland (Nevanen et al 2014). However, factors such as inconsistent funding for both sectors (Arts Council 2005), the focus on academic subjects (McLauchlan 2017) and uncertainty of the role of the artist when working in the ECEC setting (Petrie and Chambers 2010) have led to various models of how artists are involved in the ECEC setting and for how long (Remer 2010). Remer (2010) found that longer-term arts and education collaborations are more likely when leaders of arts organisations and education settings construct the polices and goals together.…”
Section: Introductionmentioning
confidence: 99%